Parameter estimation in a structured erythropoiesis model - Azmy S. Ackleh; Jeremy J. Thibodeaux (Mathematical Biosciences and Engineering)
We develop a numerical method for estimating parameters in astructured erythropoiesis model consisting of a nonlinear system ofpartial differential equations. Convergence theory for the computedparameters is provided. Numerical results for estimating the growthrate of precursor cells as a function of the erythropoietinconcentration and the decay rate of erythropoietin as a function ofthe total number of precursor cells from computationally generateddata are provided. Standard errors for such parameters are alsogiven.